(untitled) (Czech Journal of International Relations, 2013)
The present paper aims to compare the approaches of the Bush and Obama administrations towards the role of nuclear weapons in the United States security strategy. The author focuses on the Nuclear Posture Review (NPR) reports from 2001 and 2010, employing a detailed comparative analysis of their respective content as well as their implications. The analysis concentrates on broader conceptual issues as well as on the very concrete steps related to specific elements of the United States strategic arsenal. The author argues that the current political discourse, which attributes a nearly revolutionary character to the approach of the Obama administration to the United States nuclear policy, does not fully match the actual dimension of the change between the NPR of 2001 and that of 2010. In fact, the evolution of the United States nuclear strategy maintains its own dynamics in many aspects.